Vivência de pessoas com insuficiência renal crônica em tratamento hemodialítico: o cotidiano e seus significados - Oliveira, Cláudia Cássia de (2013)
In the epidemiologic transition process in Brazil, we verify the increase of diseases and non-transmissible health problems cardiovascular diseases, chronic respiratory diseases neoplasias, mellitus diabetes, arterial hypertension and chronic renal failure. In 2011, the estimated number of patients in hemodialysis was 91,314 (SBN, 2011). Changes have been occurring in chronic health conditions health systems and care processes, and involve a change in paradigm, from an essentially biological model to a bio psychosocial model. Seeking to understand psychosocial aspects of the life experience of people with Chronic Renal Failure CRF in hemodialysis treatment, we developed this research in a Substitutive Renal Therapy Center, located in Southern Minas Gerais, Brazil. It is a field research with a qualitative approach. In a first stage of the research, we performed periods of daily life observation of the patients who frequented the SRTC. In a second stage, we performed semi structured interviews with ten patients in hemodialysis treatment for at least three years. We adopted an analytical strategy with the data collected from the interviews, the Thematic Analysis, as described from Ezzy (2002). The reports from the patients showed their different life experiences in the different stages of the disease and treatment. The initial confronting of the treatment was marked by the review of their life trajectories, in addition to demanding adaptations to a new life style, with physical, psychological and social wearing, and many losses in their daily life activities. The time elapsed from the diagnosis until the stage in which they were when the interview was conducted seems to have been a soothing, an opportunity of growth, to reorganize life and develop their own manner of resilience. The participation of their family members and of the health team was showed to be relevant for the adaptation process. The hope for a transplant which would release them from hemodialysis is cited by the interviewed in different aspects. Religiosity and family are significant aspects of the patients strength in facing the wearing daily life. Possibilities and gaps in health care with a focus on the transdisciplinary action of the team and on a higher patient autonomy are discussed in the final considerations